(untitled) (Revista Cocar, 2019)
The introduction of algebra in teacher training: the normal school of São Paulo, decade of 1880 Resumo Este texto analisa os ensinos de matemática ministrados na Escola Normal de São Paulo na década de 1880. Em particular, no uso de documentação do Arquivo Público do Estado de São Paulo, o estudo atém-se aos conteúdos algébricos presentes na formação de professores primários. Que finalidades justificaram a introdução de conteúdos algébricos na formação de professores primários? A resposta para a questão advém da análise dos ensinos de Aritmética e de Geometria, que tinham a mesma finalidade daquele dado no curso secundário: a propedêutica para a escolaridade superior. Desse modo, por imitação da cultura não profissional do curso secundário, a Escola Normal de São Paulo formou os seus professores para darem aulas para crianças no âmbito de uma concepção disciplinar dos estudos de matemática. Tal é a resposta para justificar a presença dos conteúdos algébricos na formação dos professorandos. Palavras-chave: Formação de professores. Álgebra. Escola Normal. Programas de ensino. Abstract The present text is an analysis of the Mathematics teaching at Normal School of São Paulo in 1880’s. This study, in the use of documentation from the Public Archive of the State of São Paulo, focuses on the algebraic content used in the formation of elementary teachers. What were the reasons for the introduction of algebraic content in the formation of elementary teachers? The answer for this question is the same of the propose of Arithmetic and Geometry teaching in secondary school, the preparation for superior education. Thereby, mimicking the not professional culture of secondary school, Normal School of São Paulo educate their professors for teaching students in the context of disciplinary conception of the studies in Mathematics. This is the answer which justify the presence of algebraic contents in the teacher’s formation. Keywords: Formation of teachers. Algebra. Normal School.